THE EFFECT OF ABLUTION THERAPY ON IMPROVING LEARNING CONCENTRATION - Rahmadini, Dila; al-Kaf, Idrus; Nur Kholifa, Umi (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study aims to determine the effect of ablution therapy in improving the learning concentration of 12th grade students at SMAN 1 Talang Kelapa. The background of this study is the low level of student concentration as seen from the lack of focus, daydreaming behavior, and fatigue during the learning process. Ablution therapy was chosen because it is believed to have a relaxing effect and stimulation of acupuncture points that play a role in stabilizing emotions and increasing focus. This study used a quantitative approach with a one group pretest-posttest experimental design. A sample of 28 students was selected through simple random sampling technique. The research instrument is a learning concentration questionnaire that has been tested for validity and reliability. The results of data analysis using paired sample t-test and simple linear regression showed that ablution therapy had a significant effect on increasing students' learning concentration, with a significance value of 0.000 and a determination value of 93.5%. The findings suggest that ablution therapy can be an effective alternative spiritual intervention in improving learning concentration, especially for students with high academic load